2020
DOI: 10.1007/s00432-020-03149-2
|View full text |Cite|
|
Sign up to set email alerts
|

Restoration of MARCK enhances chemosensitivity in cancer

Abstract: Purpose Increased ATP-binding-cassette (ABC) transporter activity is a major cause of chemotherapy resistance in cancer. The ABC transporter family member ABCB1 is often overexpressed in colorectal cancer (CRC). Phosphatidylinositol-4,5-bisphosphat (PI(4,5)P 2)-dependent pathways are involved in the regulation of ABCB1 function. The protein Myristoylated Alanine-Rich C-Kinase Substrate (MARCKS) is a pivotal regulator of PI(4,5)P 2 and inactivated in many CRC cancers via genetic deletion or hyperphosphorylation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Whereas the functional influence of MARCKS on cellular systems extends beyond developmental and maintenance workflow, numerous studies have now indicated that anomalous expression of MARCKS is often associated with several cancers. Extensive data suggest that dysregulated MARCKS expression drives the development and progression of several solid tumors including melanoma [ 11 , 102 , 103 ], glioma [ 12 , 104 , 105 ], renal cell carcinoma [ 106 ], lung cancer [ 107 109 ], colorectal cancer [ 110 , 111 ], liver cancer [ 13 , 112 ], and breast cancer [ 113 115 ]. Similarly, aberrant MARCKS has been observed to contribute to increased cell proliferation, reduced cell death, higher rates of cell migration, invasion, and motility, and malignant transformation in several hematological malignancies (Table 1 ).…”
Section: Marcks Impacts the Development And Progression Of Blood Cancersmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas the functional influence of MARCKS on cellular systems extends beyond developmental and maintenance workflow, numerous studies have now indicated that anomalous expression of MARCKS is often associated with several cancers. Extensive data suggest that dysregulated MARCKS expression drives the development and progression of several solid tumors including melanoma [ 11 , 102 , 103 ], glioma [ 12 , 104 , 105 ], renal cell carcinoma [ 106 ], lung cancer [ 107 109 ], colorectal cancer [ 110 , 111 ], liver cancer [ 13 , 112 ], and breast cancer [ 113 115 ]. Similarly, aberrant MARCKS has been observed to contribute to increased cell proliferation, reduced cell death, higher rates of cell migration, invasion, and motility, and malignant transformation in several hematological malignancies (Table 1 ).…”
Section: Marcks Impacts the Development And Progression Of Blood Cancersmentioning
confidence: 99%
“…Within solid cancers, MARCKS has commonly been identified with a cancer-promoting role in breast cancer [ 113 115 ], lung cancer [ 107 109 ], melanoma [ 11 , 103 ], glioma [ 104 ], renal cell carcinoma [ 106 ], and liver cancer [ 13 , 112 ]. Contrarily, several research groups have observed that higher expression of MARCKS inhibits cancer development and progression in colorectal cancer [ 110 , 147 ], hepatocellular carcinoma [ 148 ], melanoma [ 149 ], and glioma [ 12 , 105 , 150 ]. Such a dual role of MARCKS has been observed in blood cancers as well.…”
Section: Marcks Impacts the Development And Progression Of Blood Cancersmentioning
confidence: 99%
“…In our research, by enrichment analysis and partial correlation analysis, we found that MARCKS was highly correlated with hub genes such as CD74 and immune cells such as DCs, which are responsible for LCH. Since MARCKS is currently viewed as a potential target for immunotherapy and chemosensitivity, it is reasonable to believe that it will also be a potential therapeutic target for LCH [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Wenzel et al identified MARCKS, also as a key factor for the membrane expression of ABCB1. They showed that functional disruption of MARCKS led to an inhibition of ABCB1 internalization, resulting in its accumulation at the plasma membrane [ 36 ]. In another study, Chai et al showed that the activation of liver PKCs led to Ezrin Thr567 phosphorylation, resulting in ABCC2 internalization [ 37 ].…”
Section: Discussionmentioning
confidence: 99%